Determination of the interface band alignment of Mg2Si/4H‐SiC heterojuction for potential photodetector application. (14th December 2021) - Liao, Yangfang; Xie, Jing; Lv, Bing; Xiao, Qingquan; Xie, Quan
Abstract : The Mg2 Si/4H‐SiC heterojunction was prepared by radio frequency (RF) magnetron sputtering technique. The binding energies of Mg 2p, Si 2p, and C 1s core levels and the maxima of valence band were measured by X‐ray photoelectron spectroscopy (XPS). Using the optical bandgap of Mg2 Si (0.78 eV) and 4H‐SiC (3.25 eV), the band offsets of valence band (VBO) and conduction band (CBO) at Mg2 Si/4H‐SiC interface were identified as 1.47 and 1.00 eV, respectively. The band alignment was evaluated to be type‐I band alignment. The Mg2 Si/4H‐SiC heterojunction could be a promising candidate for the infrared (IR) photodetector.